Physiologically based modeling of lead kinetics: a pilot study using data from a Canadian population. Issue 12 (13th November 2015) - MacMillan, John W.; Behinaein, Sepideh; Chettle, David R.; Inskip, Mike; McNeill, Fiona E.; Manton, William I.; Healey, Norm; Fisher, Mandy; Arbuckle, Tye E.; Fleming, David E. B.
Abstract : The Canadian population is currently subject to low, chronic lead exposure and an understanding of its effects is of great significance to the population's health. Abstract : The Canadian population is currently subject to low, chronic lead exposure and an understanding of its effects is of great significance to the population's health. Such low exposure is difficult to measure directly; approximation by physiologically based modeling may provide a preferable approach to population analysis. The O'Flaherty model of lead kinetics is based on an age-dependent approach to human growth and development and devotes special attention to bone turnover rates. Because lead is a bone-seeking element, the model was deemed ideal for such an analysis. Sample from 263 individuals of various ages from the Greater Toronto Area were selected to evaluate the applicability of the current version of the O'Flaherty model to populations with low lead exposure. For each individual, the input value of lead exposure was calibrated to match the output value of cortical bone lead to the individual's measured tibia lead concentration; the outputs for trabecular bone, blood, and plasma lead concentrations obtained from these calibrations were then compared with the subjects' measured calcaneus, blood, and serum lead concentrations, respectively. This indicated a need for revision of the model parameters; those for lead binding in blood and lead clearance from blood to bone were adjusted and new outputs were obtained in the same fashion as before. Model predictions of trabecular lead concentration did not agree with measurements in the calcaneus. The outputs for blood and plasma lead concentrations were highly scattered and, on an individual level, inconsistent with corresponding measurements; however, the general trends of the outputs matched those of the measurements reasonably well, which indicates that the revised blood lead binding and lead clearance parameters may be useful in future studies. Overall, the analysis showed that with the revisions to the model discussed here, the model should be a useful tool in the analysis of human lead kinetics and body burden in populations characterized by low, chronic exposure to lead from the general environment.